PHYSICAL THERAPY INTERVENTION IN BIMALLEOLAR FRACTURES - Mihaela Alina CRISTUŢĂ (Editura Universitatii Transilvania din Brasov, 2019)
This paper has observed the re-education process of motor functions after fracture. At the end of the research, the author thinks that the physical therapy intervention has contributed to the improvement of the subjects' independent performances. For a good functionality, movement coordination and re-establishing the balance, the physical therapy program is indispensable